RELEVANSI ETIKA ARISTOTELES DENGAN ETIKA PANCASILA (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Especial Target of ethics Aristoteles is orient at public bliss. Bliss like this in line with especialÂ target of ethics is in the form of â€œor especial moralâ€, that is especial and intellectual especial of moral.Â Intellectual especial pass the theoretical wisdom is whch only can be conducted by intellectual circle;Â while especial of moral pass the practical wisdom is which in this case human being have to able toÂ determine the a middle course to two both of the same deed of ekstrem throw to interfere in and able toÂ run the activity by following objective kindliness standart which is by public thought well of. AccordingÂ to Aristoteles of so that human being reach the high bliss with quality as refection dream of the idealÂ life, hence human being have to able to look into the truth. In this case anly a steel philosopher capableÂ to reach it and axecute it. That ethics Aristoteles is relevant its contents payload and in line with ethicsÂ Pancasila, what is two placing Â forward wisdom by taking one thing with another, as manifestasi senseÂ of justice, moderation, and impregnability.Keywords : ethics Aristoteles, ethics Pancasila